Evaluation of streamflow drought index in Aegean region, Turkey - Gülmez, Ayşe; Mersin, Denizhan; Vaheddoost, Babak; Safari, Mir Jafar Sadegh (My University, 2021)
Water is an invaluable substance that ensures the life cycle and hydrological events across the world. In this respect, water deficit also known as drought is a natural disaster-related to water scarcity in time and space. Although there is no solid definition for the phenomenon, the outcome of repeated wet and dry spells causes economic, social, and political problems on a regional, countrywide, and worldwide scale. In this study, drought associated with the streamflow in the Aegean region, which has an important economic, historical and socio-cultural role in western Turkey, is investigated through the well-known streamflow drought index (SDI). Therefore, average discharge in the Çiçekli-Nif, Beşdeğirmenler-Dandalas, Bebekler-Rahmanlar and Koçarlı-Köprübaşı station respectively related to on Gediz, Büyük Menderes and Küçük Menderes basins were used. Then SDI with 1, 3, 6,12 months moving average is acquired to express the drought severity associated with the streamflow in the basins. Results showed that the SDI values in all of the stations together with the 1, 3, 6, and 12- month moving averages depicts similar results and no abnormal situation exists during the study period.
Bildiri - Yayımlanmış
Keywords: Drought; Hydrology; Water resources; Civil engineering